Perancangan dan Implementasi Sistem Pengukuran Ketinggian dan Volume Air pada Tandon Berbasis Sensor Jarak dan IoT dengan Monitoring melalui Aplikasi Mobile - Moh. Dwi Rizkiyanto; Aria Riskya Putra; Deanda Yoga Nur Ikhsan; Friska Ayu Fitrianti (Politeknik Negeri Semarang, 2026)
Water plays a vital role in daily life; however, monitoring water filling in reservoirs is still commonly performed manually, leading to inadequate supervision, water overflow, and increased operational costs. This study aims to develop an Internet of Things (IoT)–based system for measuring water level and volume in reservoirs using a distance sensor that can be monitored through a mobile application. The system employs an HC-SR04 ultrasonic sensor to detect water height, an ESP32 microcontroller for data processing, and the Blynk application for real-time data visualization. System calibration was carried out using a measuring cup as a reference standard with volume variations ranging from 100 ml to 500 ml. The experimental results show that the proposed system achieves good measurement performance with an average error of 1.87%, where higher errors occur at lower volumes and decrease as the measured volume increases. These results indicate that the developed system is sufficiently accurate and suitable for implementation as an IoT-based solution for water volume monitoring in reservoirs.